Breeding and production performance profile of Black Bengal goats in rural areas of Mymensingh in Bangladesh (Bangladesh Journal of Animal Science, 2016)
The present study was conducted to know the breeding and performance profile of Black Bengal goat in 4 upazila (Mymensingh Sadar, Fulbaria, Trishal and Muktagacha) of Mymensingh district. The data were collected using a pre-tested questionnaire from 100 goat rearers. The questionnaire included primary information about goat owners, total number of goats, color pattern, birth information, fate of male kids, weight of kids, breeding system and source of breeding males, breeding cost, litter size, kid mortality, some management parameters on goat and goat rearing system under rural condition. On an average, goat per family at Mymensingh district was found to be 3.56 ±1.77 where the percentage of does and bucks were 90.61% and 9.39% respectively. Most of the farmers were found not to keep male kid for bad odor and difficult management and hence castrate them. Almost all farmers depend on natural mating to serve their does by passing a significant distance. The average service charge was found BDT 70.90±1.77, which differs significantly (P< 0.05) among four upazilas. No significant difference was found in performance of goats among four upazilas. The average body weight at 3 and 6 months of age of female goats were 4.67 ± 0.15 and 7.12±0.14 kg respectively. The average litter size was found 1.76±0.75 and the average kid mortality rate was 12.88% in Mymensingh district. From this study, it became evident that acute shortage of Black Bengal breeding bucks exists in the rural areas which may represent the overall situation of the country.Bang. J. Anim. Sci. 2016. 45 (2): 46-51